PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY BERBANTU APLIKASI ASSEMBLR EDU PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SDN 10 SITIUNG - Riyadi Saputra; Zumrotun Lutfiah; Puja Rafa Rigeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is being undertaken by educators who lack the use of learning media and tend to be monotonous in the learning process so that students are difficult to understand the learning material and are prone to boredom in following learning process. The aim of this research is to know the development of Augmented Reality-based learning media with the help of the application of Assemblr Edu on learning Pancasila Education Class V SDN 10 Sites that are valid, practical, and effective. The ADDIE model has five stages: Analyze, Design, Development, Implementation, Evaluation. The Analyze stage, at this stage is performed needs analysis, characteristics analysis of students, and material analysis. As for the results of the development of Augmented Reality based learning media using the Edu Asemblr application obtained from a four-person validator, the augmented reality-based learning media achieved a percentage with an average of 87.5% with a very valid category. The practicality results assessed from the educator's response lift received a percent of 90.6% with a highly practical category and the student's responsive lift achieves a percentual with a mean of 89.22% with the category very practical. The effectiveness results of 25 pupils who followed learning using developed media were stated to be 80.8% accurate so that augmented-reality learning media based using the Assembr edu application was categorized as very effective.